Factors associated with repeat abortion among women seeking abortion in public clinic of Kathmandu. - Maharjan, Sajana (2016)
Summary: Repeat abortion is the termination of pregnancy intentionally for second or more times. It is the indicator of unintended pregnancy and ineffective post abortion contraceptive use. It is one of the neglected aspects of abortion with very limited studies. The aim of the study is to find out the proportion of repeat abortion and its associated factors. The study was cross sectional study. Two hundred and fifty five women seeking abortion at Paropakar Maternity and Women's hospital were interviewed during two months period of data collection. Women seeking abortion due to therapeutic reason (risk to mother or child health) and rape case were excluded in the study. Exit interview using semi-structured questionnaire was conducted by researcher and one trained female interviewer in private area of hospital. Collected data were entered in EpiData 3.1 and SPSS 20 version was used for analysis. Chi square test was done to examine binary association between dependent variable and independent variables and multiple logistic regression analysis was done to identify risk factors for repeat abortion. Out of 255 women, nearly one third (31.8%) of women sought for repeat abortion. Compared to women seeking first abortion, women seeking repeat abortion were more likely to be older (32.1 ± 5.5 verses 28.3 ± 5.8; p< 0.001). Women seeking repeat abortion were no different from first time abortion-seeking women in socio demographic characteristics like education and occupation of woman or her partner and in number of children. In bivariate analysis, women with repeat abortion were more likely to intend no child in future (OR 2.14; 95% CI, 1.13-4.08) and report completed family size as reason for abortion (OR 2.04;95% CI, 1.11-3.74) compared to women seeking first time abortion. It was found that 30.9% of women seeking repeat abortion and 23.6% of first time abortion seeking women have used modern contraceptive at the time of index pregnancy. The difference in contraceptive use at the time of index pregnancy between these two groups of women was not statistically significant. And in six months prior to index pregnancy, repeat abortion women have used modern contraceptive more than first time abortion seeking women (OR 1.78; 95% CI:1.043.01).This finding shows that women seeking repeat abortion were no different in use of contraceptive compared to first time abortion seeking women, rather have used it more in last six months period. Similarly, no statistical difference was found between these groups of women regarding post abortion contraceptive use. Older age, decision of abortion taken by woman herself only without consent of her partner was found to be risk factor for repeat abortion in multivariate analysis. Educational status, occupation, parity, use of contraceptive was not found significantly associated for repeat abortion. The time of previous abortion was found to be within one year in about one third of women (29.7%) and half of women had abortion within last two years (51.9%). Among all abortion-seeking women, only 39.6% have heard about emergency contraceptive. The most common reason for non use of contraceptive during the time of index pregnancy was experience of side effects (31.1%) followed by taking chance/carelessness (21%), infrequent sex (15.1%), breastfeeding (10.1%), fear of side effects (8.4%), less perceived risk of pregnancy (5%) and others (6.7%). Pregnancy despite use of modern contraceptive was mainly due to improper use of method. Irregular use of pills was the common reason for pregnancy in women using modern contraceptive that shows the need to focus on counseling on regular use of pills. Since decision of abortion taken by woman only was found as risk factor for abortion after controlling other variables, further studies to explore relationship status with partner need to be explored to assess risk factor for repeat abortion.